Faktor-Faktor Yang Mempengaruhi Keputusan Pembelian Tiket Pesawat Di PT Wahyu Septyan Tour Dan Travel Kota Bengkulu - Junaidah Junaidah; Eska Prima Prima Monique Damarsiwi; Wagini Wagini (UNIVED Press, 2023)
Along with the development of the times, people want to use transportation to make their journey easier. Air tickets sold by PT Wahyu Septyan Tour and Travel Bengkulu city can make your trip both national and international easier. The purpose of the study was to determine the effect of brand image, price, promotion, and service quality on the decision to purchase airline tickets at PT Wahyu Septyan Tour and Travel in Bengkulu city. The type of research used is quantitative. The data analysis method used is multiple linear regression. The test results obtained are: 1) The partial test results show that the brand image (x1) has a significance value of 0.036 <0.05. Price (x2) has a significance value of 0.001 < 0.05. Promotion (x3) has a significance value of 0.002 < 0.05. and service quality (x4) has a significance value of 0.037 <0.05. Thus, the results of the t-test (partial) indicate that there is a positive and significant influence of brand image, price, promotion, and service quality variables on purchasing decisions at PT Wahyu Septyan Tour and Travel in Bengkulu city. 2). Simultaneous test results with the provisions of significance <0.05. The significance probability number 0.000 < 0.05 means that brand image, price, promotion, and service quality simultaneously affect the decision to purchase airline tickets at PT Wahyu Septyan Tour and Travel in Bengkulu city.